2014
DOI: 10.15171/ijhpm.2015.05
|View full text |Cite
|
Sign up to set email alerts
|

Inequity in hospitalization care: a study on utilization of healthcare services in West Bengal, India

Abstract: Background: Out of eight commonly agreed Millennium Development Goals (MDG), six are related to the attainment of Universal Health Coverage (UHC) throughout the globe. This universalization of health status suggests policies to narrow the gap in access and benefit sharing between different socially and economically underprivileged classes with that of the better placed ones and a consequent expansion of subsidized healthcare appears to be a common feature for most of the developing nations. The National Health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 13 publications
0
41
0
Order By: Relevance
“…Thus, subjects with a serious disease like ESRD with the NHI faced a much greater economic burden than those with MA. Subjects with high OOP expenditure are more likely to face the risk of CHI [25][26][27][28]. CHE was compared between subjects with MA (n=68) and…”
Section: Discussionmentioning
confidence: 99%
“…Thus, subjects with a serious disease like ESRD with the NHI faced a much greater economic burden than those with MA. Subjects with high OOP expenditure are more likely to face the risk of CHI [25][26][27][28]. CHE was compared between subjects with MA (n=68) and…”
Section: Discussionmentioning
confidence: 99%
“…Thus, subjects with a serious disease like ESRD with the NHI faced a much greater economic burden than those with MA. Furthermore, subjects with high OOP expenditure are more likely to face the risk of CHE [25][26][27][28]. CHE was compared between subjects with NHI under the median of household income decile and with MA.…”
Section: Discussionmentioning
confidence: 99%
“…Further, NFHS 4 does not provide any information on the actual cost of delivery care at the public health centre. Hence in line with previous literature, we have used OOP payment on delivery care in private health centres as the proxy for the actual cost of delivery care in public health centres [44][45].…”
Section: Oop Payment and Cost Of Service On Institutional Deliverymentioning
confidence: 99%
“…A recent study found a pro-rich distribution of public subsidy for inpatient care of non-communicable diseases (NCDs) among elderly [43]. In West Bengal, the bene t of public subsidy was highest for individuals belonging to lower-middle group in rural areas and upper-middle income group in urban areas [44]. In 2004, for inpatient care, the share of public subsidy was maximum for poorest section (41.5%) in Tamil Nadu, lower middle in West Bengal (32.3%) and richest section (38.9%) in Rajasthan.…”
Section: Introductionmentioning
confidence: 99%